2021
DOI: 10.3389/fsufs.2021.677580
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Parameters of Nitrate Absorption by Adult Coffee Trees

Abstract: Nitrogen, the most demanded nutrient by coffee plants, has a rate of recovery from the soil of about 50%. Because of that high doses of nitrogenous fertilizers are used to reach high production, and consequently high amounts of N are lost to the environment. Knowing the kinetic parameters of nitrate (NO3-) absorption over the fruit development cycle is important as a mean of achieve more adjusted fertilizer doses and better recovery rates for the N applied as fertilizers. This study aimed determining the kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…The current findings are also in agreement with Poncet et al (2024), Bracken et al [ 3 ], Castillo and Andrade [ 5 ], Wegari and Amin [ 59 ], Bohórquez et al [ 60 ], Silva et al [ 61 ], Defrenet et al [ 62 ], who reported that top root length exhibits significant variation in different plant growth media compositions. This might be chiefly due to the fertility variation of the organic amendment compositions [ 63 ] and growing condition difference [ 64 ] that enabled the seedling taproot to penetrate deeply and store assimilates from source to sink.…”
Section: Resultssupporting
confidence: 92%
“…The current findings are also in agreement with Poncet et al (2024), Bracken et al [ 3 ], Castillo and Andrade [ 5 ], Wegari and Amin [ 59 ], Bohórquez et al [ 60 ], Silva et al [ 61 ], Defrenet et al [ 62 ], who reported that top root length exhibits significant variation in different plant growth media compositions. This might be chiefly due to the fertility variation of the organic amendment compositions [ 63 ] and growing condition difference [ 64 ] that enabled the seedling taproot to penetrate deeply and store assimilates from source to sink.…”
Section: Resultssupporting
confidence: 92%